2006
DOI: 10.1002/ijc.22136
|View full text |Cite
|
Sign up to set email alerts
|

CYP2A13 expressed in human bladder metabolically activates 4‐aminobiphenyl

Abstract: Cigarette smoking is the predominant risk factor for bladder cancer. Aromatic amines such as 4-aminobiphenyl (ABP) are the major carcinogens found in tobacco smoke. Although it is generally accepted that ABP is metabolically activated via N-hydroxylation by CYP1A2 in human liver, previous studies using Cyp1a2-null mice indicated the involvement of other enzyme(s). Here we found that CYP2A13 can metabolically activate ABP to show genotoxicity by Umu assay. The Km and Vmax values for ABP N-hydroxylation by recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
66
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 34 publications
3
66
0
Order By: Relevance
“…Total RNA was isolated from human hepatocytes or mouse liver using RNAiso (Takara) following the manufacturer's protocol, and cDNA was synthesized as described previously [15]. The primers for human CYP2A6 [15] and human GAPDH [16] were described previously.…”
Section: Real-time Rt-pcr Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA was isolated from human hepatocytes or mouse liver using RNAiso (Takara) following the manufacturer's protocol, and cDNA was synthesized as described previously [15]. The primers for human CYP2A6 [15] and human GAPDH [16] were described previously.…”
Section: Real-time Rt-pcr Analysesmentioning
confidence: 99%
“…The primers for human CYP2A6 [15] and human GAPDH [16] were described previously. The forward and reverse primers for mouse NAD(P)H:quinone oxidoreductase 1 (NQO1) were 5'-CCCTGATTGTACTGGCCCATT-3' and 5'-CGTCCTTCCTTATATGCTAG-3', respectively.…”
Section: Real-time Rt-pcr Analysesmentioning
confidence: 99%
“…CYP2A6 hepatic over expression is elevated in hepatocellular carcinoma associated with cirrhosis and chronic inflammation [10]. Inhibition of CYP2A by chalepensin causes cytotoxicity in carcinoma cell lines and this might have significance in target organs expressing CYP2A6, like testis, ovary, uterus and liver [11].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies demonstrated that CYP2A13 is the most efficient human P450 enzyme for the metabolic activation of NNK, a tobacco-specific toxicant and suspected human carcinogen (Su et al, 2000). CYP2A13 can also metabolically activate 4-aminobiphenyl, another carcinogen in cigarette smoke (Nakajima et al, 2006). In addition, CYP2A13 is highly efficient in metabolizing nicotine (Bao et al, 2005) as well as the metabolic activation of aflatoxin B 1 , naphthalene, and styrene (Fukami et al, 2008).…”
Section: Introductionmentioning
confidence: 99%